Três ensaios sobre capital humano e seus efeitos no crescimento econômico e na sobrevivência de empresas - Saraiva, Maurício Vitorino (2022)
This thesis is composed of three essays in the area of the regional economics that explore in a complementary way the spatial distribution of quality and quantity of human capital and their relation with economic growth and business survival. The first essay is a preliminary step and has investigative nature, making a spatial inquiry on the relation between human capital and economic growth in Brazil, in the period from 2009 to 2017. At first, we created a multidimensional proxy for quality of human capital, while in the case of quantity a usually found in literature proxy is used. The results of AEDE indicate that quantity and human capital quality are spatially related to the major economic growth, finding the presence of spatial autocorrelation and diverse clusters. In order to investigate those relations, on the second essay, the importance of quantity and quality of human capital for economic growth is evaluated, proposing an extension of the Mankiw, Romer e Weil (1992) model, with the inclusion of the quality aspect as a factor capable of boosting the regional economy. An econometric spatial panel is used for the microregions of the country from 2009 to 2017. All estimated coefficients follow the expected signals by the proposed model and the results reassure the importance of both aspects of human capital for economic growth. Both direct and indirect effects are found, suggesting that human capital is important to the region itself and mainly to neighboring localities. The third essay analyzes the importance of quantity and quality of human capital to the survival of new businesses. We used a sample of identified microdata from RAIS containing information of all formal workers from 27.838 establishments created in 2009 at Rio Grande do Sul. Those establishments were followed up to 2017, constituting a panel data for the application of non-parametric and parametric estimation functions of survival of the companies. The results show that both human capital aspects are key factors for the longevity of companies of the business, services and industry segments. By the end of the three essays, in general, we concluded that public policies should implement in a strategic way the regional actions to stimulate development and reduce the disparities of human capital, as a way to oppose the regional economic disparities and promote economic growth.